Oral health and dental care in pregnant women: bibliometric study, systematic review, and content analysis - Almario-Barrera, Andrea Johanna; Acevedo-Argüello, César; Villarreal-Neira, Camila; Morales-Borrero, Carolina; Concha-Sánchez, Sonia Constanza (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: the oral condition of pregnant women and the attention it needs affect the overall health of these women and their children. A variety of perspectives have been used to understand and approach research on this field. The objectives of this study were: conduct a bibliometric analysis, assess the quality of the available evidence, and conduct content analysis of articles related to the topics. Methodology: publications related to the topics were identified through a systematic search of the literature, identifying authors, years, and countries with the most publications; in addition, quality of the reports was assessed through the STROBE Guide on the studies that were retrieved in full text, conducting content analysis on thematic, methodological, and epistemological aspects. Results: the systematic review was conducted in three databases (PubMed, Scopus, and Web of Science). Institutions, authors, institutional affiliation, and co-authorship networks were identified with the bibliometric analysis. The systematic review showed predominance of cross-sectional observational studies; there were few controlled clinical trials and they generally emphasized treatments for periodontal disease in pregnant women. The evidence on this subject tends to be low. Content analysis showed that, in ontological terms, research focuses on three main areas: a) biological differences between men and women; b) impact of pregnant women’s oral health on the oral and overall health of their babies, c) relationship between pregnancy, oral health, and its impact on the oral and overall health of women. Few studies explore social determinants. In epistemological terms, studies from positivist perspectives were predominant. In methodological terms, the emphasis is placed on research with quantitative approaches. Conclusion: it is necessary to strengthen the relationship between biological and social aspects of pregnant women’s oral health and dental care from different epistemological perspectives, seeking a comprehensive view of these aspects and improving dental care in pregnant women